TINGKAT KETERAMPILAN SERVIS ATAS, DAN PASSING BAWAH SISWA PUTRA PESERTA EKTRAKURIKULER BOLA VOLI SMA NEGERI ACEH BESAR - Junaidi; Yudi Ikhwani (Jurnal Penjaskesrek, 2018)
The essence of volleyball games is physical activity based on the spirit of struggle against oneself and others who must be guided by the knighthood, it is intended that in playing volleyball one must uphold the values ​​of honesty, confidence, cooperation, discipline, creativity, sportsmanship, responsibility and courage. This study aims to determine the level of service skills above, and underhand passing of male students of volleyball extracurricular participants in Aceh Besar State High School. This research is a descriptive study. Subjects in this study were male students participating in volleyball extracurricular activities in Aceh Besar State High School. The instrument used is a volleyball playing skill test from Richard H. Cox using 2 test items, namely (AAHPER serving accuracy test), (Brumbach forearm pass wall-volley). service skill level test results for male students of volleyball extracurricular participants in SMA Negeri 1 Aceh Besar there are 2 students (10%) in very good category, 2 students (10%) in good category, 10 students (50%) in sufficient category, 6 students (30%) categorized as lacking, and 0 students (0%) categorized as poor. Whereas for the results of the test the level of under passing skills of male students of volleyball extracurricular participants in SMK Negeri 1 Pandak, Bantul Regency, there are 0 students (0%) in very good category, 10 students (50%) in good category, 6 students (30%) in sufficient category , 1 student (5%) is categorized as lacking, and 3 students (15%) are categorized as poor. The conclusion from the results of the research is that the level of service skills for male students of volleyball extracurricular participants in Aceh Besar State High School is sufficient, and lower passing skills are in good category. Abstrak Hakikat dari permainan bola voli adalah kegiatan jasmani yang dilandasi semangat perjuangan melawan diri sendiri dan orang lain yang harus dilandani jiwa ksatria, dimaksudkan bahwa dalam bermain bola voli seseorang harus menjunjung tinggi nilai kejujuran, percaya diri, kerjasama, disiplin, kreatif, sportifitas, tanggung jawab, dan keberanian. Penelitian ini bertujuan untuk mengetahui tingkat keterampilan servis atas, dan passing bawah siswa putra peserta ekstrakurikuler bola voli di SMA Negeri Aceh Besar Penelitian ini merupakan penelitian deskriptif. Subjek dalam penelitian ini adalah siswa putra peserta kegiatan ekstrakurikuler bola voli di SMA Negeri Aceh Besar. Instrumen yang digunakan yaitu tes keterampilan bermain bola voli dari Richard H. Cox dengan menggunakan 2 butir tes, yaitu (AAHPER serving accuracy test), (Brumbach forearm pass wall-volley). hasil tes tingkat keterampilan servis atas siswa putra peserta ekstrakurikuler bola voli di SMA Negeri 1 Aceh Besar terdapat terdapat 2 siswa (10%) berkategori baik sekali, 2 siswa (10%) berkategori baik, 10 siswa (50%) berkategori cukup, 6 siswa (30%) berkategori kurang, dan 0 siswa (0%) berkategori kurang sekali. Sedangkan untuk hasil tes tingkat keterampilan passing bawah siswa putra peserta ekstrakurikuler bola voli di SMK Negeri 1 Pandak Kabupaten Bantul terdapat bahwa 0 siswa (0%) berkategori baik sekali, 10 siswa (50%) berkategori baik, 6 siswa (30%) berkategori cukup, 1 siswa (5%) berkategori kurang, dan 3 siswa (15%) berkategori kurang sekali. Kesimpulan dari hasil penelitian adalah tingkat keterampilan servis atas siswa putra peserta ekstrakurikuler bola voli di SMA Negeri Aceh Besar adalah cukup, dan keterampilan passing bawah berkategori baik. Kata Kunci: keterampilan, servis atas, passing bawah, dan siswa SMA